Two-Dimensional Directions Determination for GNSS Spoofing Source Based on MEMS-Based Dual-GNSS/INS Integration - Chengzhong Zhang; Dingjie Wang; Jie Wu (Remote Sensing)
Satellite navigation spoofing is a major challenge in the field of satellite/inertial integrated navigation security. To effectively enhance the anti-spoofing capability of a low-cost GNSS/MEMS-SINS integrated navigation system, this paper proposes a method integrating a dual-antenna global navigation satellite system (GNSS) and a micro-inertial measurement unit (MIMU) to determine the two-dimensional directions of spoofing signal sources. The proposed method evaluates whether the single-difference carrier-phase measurements conform to the corresponding directions given in ephemeris files and employs micro-inertial navigation technology to determine the two-dimensional directions of the signal source. Based on a set of short-baseline dual-station measurements, the accuracy of the proposed method in determining the two-dimensional azimuths of satellites in synchronous orbits is verified, and the deviation from the real value is evaluated. The experimental results show that the proposed method can effectively identify the spoofed satellite signals while providing high-precision direction information at three different distances: 100 m, 10 km, and 36,000 km. The two-dimensional angle errors do not exceed 0.2 rad, 0.05 rad, and 0.01 rad, respectively.